The development an Outcome-Based Education (OBE) system for measuring student programme attainment / Norhalida Othman ... [et al.] - Othman, Norhalida; Mat Saat, Ezril Hisham; Muhamad, Nur Amalina; Khairul Anuar, Hafizah; Abdul Majid, Masmaria (UiTM Cawangan Perlis, 2024)
The advancement of Outcome-Based Education (OBE) in higher education necessitates efficient systems for assessing and managing student program outcomes. Traditional methods often fall short in providing integrated and streamlined approaches to track and evaluate student attainment, posing a significant challenge for academic institutions. This study introduces the development of the College of Engineering Academic Information Management System (CO-AIMS) in School of Electrical Engineering, College of Engineering, UiTM Pasir Gudang to address these issues. Utilizing the Rapid Application Development (RAD) model, CO-AIMS is designed to measure Program Outcomes (POs) through advanced computing technologies. The system offers robust functionalities that allow academic advisors to monitor and analyze student performance at individual, semester, and cohort levels. By enabling data-driven decision-making and fostering continuous improvement in educational practices, CO-AIMS aligns student achievements with institutional objectives more effectively. The implementation of this system not only enhances the management of academic pathways but also bridges critical gaps in current methodologies, demonstrating its transformative potential in educational assessment and management.